Building Justice And Public Trust: Improving The Quality Of Judges Decision In Criminal Context - Waruwu, Riki Perdana Raya; Rabbani, Deden Rafi Syafiq (Veteran Law Review, 2024)
In the process of adjudicating cases, the substantial values ​​in judge decisions are often debated in the public sphere because of the disparity in several criminal decisions with similar events and light sentences (strafmaat) to law enforcement officers who commit corruption crimes, such as decisions at the appeals level. against a former prosecutor named Pinangki Sirna Malasari. Through conceptual approach, statute approach, and case approach, this paper attempts to answer two important questions, First, how to create quality decisions for the realization of justice and public trust? Second, how does the judiciary respond to public protests the court's decision which is considered to have imposed a low sentence on perpetrators of corruption? As a result of this paper, that quality decisions are made by judges by paying attention to legal justice, moral justice, and social justice with paying attention to the purpose of "preventive" sentencing to protect the community by placing criminals separately. from society and the purpose of "deterrence" sentencing is to create fear of committing crimes that can be distinguished for individuals, the public, and the long term. In addition, the judiciary should respond to public protests by establishing Special Guidelines in the Formulation of the Criminal Chamber of the Supreme Court which must be followed by judges.